Investigation of (Mo, W)C Based Cemented Carbides - Moien, M.; Alizadeh, E. (Asian Journal of Chemistry, 2010)
This work reports a process for the production of an alloy powder (Mo, W) and a hard solid solution (Mo, WC). The process comprises reducing a mixture of molybdenum oxide or hydroxide and tungsten oxide or hydroxide to form an alloy powder and subjecting the alloy powder to carburization. Some typical characteristics of the (Mo, W)C based cemented carbide alloys have also been studied.